Efficacy of Dexmedetomidine Versus Midazolam For Early Extubation in Critically Ill Agitated Patients Undergoing Weaning Introduction - Khan, Momal Jaleel; Sadaf, Sairah (Biological and Clinical Sciences Research Journal, 2025)
Effective sedation is essential for weaning and extubation in critically ill patients. Dexmedetomidine and midazolam are commonly used sedatives in intensive care units (ICUs). While dexmedetomidine has shown advantages in terms of sedation quality and hemodynamic stability, comparative data in the Pakistani ICU setting remains limited. Objective: To compare the efficacy and safety of dexmedetomidine and midazolam for sedation during weaning and early extubation in critically ill, agitated patients in the ICU. Methods: This prospective randomized controlled trial was conducted at Sheikh Zayed Medical College/Hospital, Rahim Yar Khan. A total of 60 patients were randomized into two groups: Group D (dexmedetomidine, n=30) and Group M (midazolam, n=30). Sedation was titrated to achieve target Ramsay Sedation Scale (RSS) scores of 3–4. Time to extubation, sedation quality, hemodynamic parameters, and adverse events were recorded. Statistical analysis was performed using SPSS version 26, with a p-value ≤0.05 considered significant. Results: The mean time to extubation was significantly shorter in Group D (21.4 ± 5.6 hours) compared to Group M (30.8 ± 8.3 hours, p<0.001). Sedation quality, measured using RSS, was superior in Group D, with higher scores at 6 hours (4.7 ± 0.4 vs. 3.9 ± 0.6, p<0.001). Hemodynamic stability was better in Group D, with a lower mean heart rate (76.4 ± 8.1 beats/min vs. 84.5 ± 9.3 beats/min, p=0.012) and higher mean arterial pressure (85.2 ± 6.4 mmHg vs. 80.8 ± 5.9 mmHg, p=0.026). Adverse events, including bradycardia (23.3% vs. 10%) was higher in group D and oxygen desaturation (3.3% vs. 10%), were lower in Group D, though differences were not statistically significant. Conclusion: Dexmedetomidine demonstrated superior sedation quality, faster extubation, and better hemodynamic stability compared to midazolam, with minimal adverse events. These findings support dexmedetomidine as a safer and more effective alternative for sedation during weaning in critically ill patients. Further research is warranted to validate these findings and assess cost-effectiveness in resource-limited settings.